Lesions mimicking lacrimal gland pleomorphic adenoma. Issue 11 (20th October 2010) - Prabhakaran, Venkatesh C; Cannon, Paul S; McNab, Alan; Davis, Garry; O'Donnell, Brett; Dolman, Peter J; Ghabrial, Raf; Selva, Dinesh
Abstract : Aim: To report a series of patients with lacrimal gland lesions simulating the clinicoradiological features of lacrimal gland pleomorphic adenoma (LGPA). Methods: Multicentre retrospective, interventional case series. Clinical records of all patients with lesions mimicking LGPA seen in five orbital units were reviewed. Results: The study included 14 patients (seven men and seven women) with a mean age of 50.9 years. The diagnosis of LGPA was made in all cases by experienced orbital surgeons, based on clinicoradiological features, and lacrimal gland excision was performed. Postoperative histology revealed lymphoma (four patients), chronic dacryoadenitis (three patients), adenoid cystic carcinoma (two patients), Sjogren's syndrome (two patients), cavernous haemangioma (one patient), benign lymphoid hyperplasia (one patient) and granulomatous dacryoadenitis (one patient). Comparison with the total number of histologically confirmed LGPA cases seen during the study period revealed that 22.6% of cases of suspected LGPA were misdiagnosed based on clinicoradiological criteria. Conclusions: Many different lesions may mimic the clinicoradiological features of LGPA. The accepted clinicoradiological criteria used for the diagnosis of LGPA have a high false-positive rate, even in experienced hands. Based on this study, the authors believe that fine-needle aspiration biopsy or intraoperative biopsy and frozen section diagnosis may help reduce unnecessary lacrimal gland excision.